Coherent excitation of a two-state system by a train of short pulses - VITANOV,NV; KNIGHT,PL (Physical Review A: Atomic, Molecular and Optical Physics, 1995)
A theoretical nonperturbative study of the coherent excitation of a two-state system by N consecutive equally spaced identical pulses is presented. General relations between the evolution matrix elements in the cases of one and N pulses are obtained in a closed form. For pulse envelopes allowing analytical solutions, these relations enable analytical treatment of pulse-train excitation; for pulses that can only be treated numerically, they shorten the computations by a factor of N. The relations show that the multiple-pulse excitation of a two-state system can be considered as a quantum analog of the diffraction grating. The interaction dynamics substantially depends on the way the train is produced because the phase shift that is accumulated by the probability amplitudes due to the free evolution of the system during and between the pulses differs. In the limit of weak excitation, the results recover earlier conclusions based on perturbative treatments. Simple formulas are derived for the conditions for complete population inversion (CPI) and complete population return (CPR), which differ from the single-pulse ones. These general results are applied to four particular cases that allow analytical solutions: resonant, rectangular, Rosen-Zener, and Allen-Eberly pulses. A common feature in all these cases is that the number and the amplitude of oscillations in the state populations increase with the number of pulses, while their width decreases. For rectangular pulses, CPI is possible below a given value of the ratio between the detuning and the pulse area; this value increases nearly linearly with the number of pulses.For the Rosen-Zener model, CPI is found to be possible for two and more pulses, while it is impossible for a single non-resonant pulse. It is shown that for a given number of pulses there is an upper limit on the detuning for which CPI can be observed; this limit increases logarithmically with the number of pulses. For the Allen-Eberly model, CPR is esta